2017
DOI: 10.1080/19396368.2017.1410591
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormone binding globulin - an important biomarker for predicting PCOS risk: A systematic review and meta-analysis

Abstract: Sex hormone-binding globulin (SHBG) is a glycoprotein which regulates bioavailability of sex steroid hormones. Interest in SHBG has escalated in recent years because of its inverse association with polycystic ovary syndrome (PCOS), obesity, insulin resistance, metabolic syndrome, and diabetes type II. This meta-analysis was performed to examine the associations of SHBG with PCOS and to correlate serum SHBG levels with various PCOS associated endocrine and metabolic dysregulation as well as to determine the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(81 citation statements)
references
References 69 publications
1
61
1
6
Order By: Relevance
“…Circulating SHBGs are consistently decreased in PCOS contributing to the increased FTI [28] and the decrease correlates with insulin resistance [29]. The baseline Hcy values of our patients correlated negatively with the concentration of SHBG, which is a new finding of this study.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Circulating SHBGs are consistently decreased in PCOS contributing to the increased FTI [28] and the decrease correlates with insulin resistance [29]. The baseline Hcy values of our patients correlated negatively with the concentration of SHBG, which is a new finding of this study.…”
Section: Discussionsupporting
confidence: 63%
“…A total of 33 PCOS ladies (mean age 26.8, range [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] were enrolled between June 2017 and October 2018, and one patient withdrew her participation for personal reasons after the basal visit. Out of 32 patients randomized, 22 entered the active treatment group, and 10 the no treatment group.…”
Section: Resultsmentioning
confidence: 99%
“…In PCOS women, the serum levels of sex hormone binding globulin (SHBG) tend to be decreased, which contributes to an increase in free testosterone (Nestler et al 1991;Fan et al 2013;Azziz et al 2016;Deswal et al 2018), the biologically active form of the hormone (Burtis et al 2008). This is believed to happen because insulin inhibits SHBG production by hepatocytes, a mechanism that may be exacerbated in women with PCOS due to hyperinsulinemia (Nestler et al 1991;Bartha et al 2000;Azziz et al 2016).…”
Section: Pathophysiology Of Pcosmentioning
confidence: 99%
“…Moreover, higher levels of SHBG were associated with lower BMI, abdominal circumference, waist to hip ratio, leptin levels and adiposity (visceral and subcutaneous adipose tissue measured by magnetic resonance imaging). Deswal et al (2018) have analyzed 10 studies about the effects of therapeutic interventions (with inositol, metformin, oral contraceptives, rosiglitazone, omega 3 or arcabose) on SHBG levels in women with PCOS, and have observed that the increase of SHBG levels is associated to an improvement in endocrine and metabolic parameters in these women.…”
Section: Pathophysiology Of Pcosmentioning
confidence: 99%
“…Ці порушення спричиняють виникнення гормонального дисбалансу, що сприяє підвищенню концентрації андрогенів над естрогенами. Як відомо, для більшості жінок із СПКЯ характерна інсулінорезистентність, в результаті чого виникає компенсаторна гіперінсулінемія, яка сприяє підвищеному виробленню андрогенів в яєчниках та надниркових залозах, що підвищує біодоступність андрогенів за рахунок зниження концентрації глобуліну, що зв'язує статеві гормони [19][20][21][22]. Важливе місце в патогенезі СПКЯ відіграє ожиріння, при якому порушується толерантність до глюкози за діабетичним типом, розвиваються інсулінорезистентність та компенсаторна гіперінсулінемія.…”
unclassified